Increased perceptual distraction and task demand enhances gaze and non-biological cuing effects. Issue 2 (February 2021) - Gregory, Samantha EA; Jackson, Margaret C
This study aims to improve understanding of how distracting information and target task demands influence the strength of gaze and non-biological (arrow and moving line) cuing effects. Using known non-predictive central cues, we manipulated the degree of distraction from additional information presented on the other side of the target, and target task difficulty. In Experiment 1, we used the traditional unilateral cuing task, where participants state the location of an asterisk and the non-target location is empty (no distraction). Experiment 2 comprised a harder localisation task (which side contains an embedded oddball item) and presented distracting target-related information on the other side. In Experiment 3, we used a discrimination task (upright or inverted embedded T) with distracter information that was unrelated or related to the target (low vs. high distraction, respectively). We found that the magnitude of cuing scaled with the degree of combined distraction and task demands, increasing up to six-fold from Experiments 1 and 2 to the high-distraction condition in Experiment 3. Thus, depleting attentional resources in this manner appears to weaken the ability to ignore uninformative directional cues. Findings are discussed within the framework of a resource-limited account of cue inhibition.